ANALISIS KOMPARASI MAKNA RASISME PADA FILM HIDDEN FIGURES DAN FILM JUST MERCY - Siska Rahayu Permata Bunda; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Racism is a difference in treatment and equality against certain groups, this phenomenon often occurs, causing various kinds of conflicts in society. Theodore Melfi as the director of Hidden Figures and Destin Daniel Cretton, the director of the film Just Mercy, depicts a visualization portrait of the issues of racism in American society with a different background through cinematography. The purpose of this study is to find out how the meaning of denotation, the meaning of connotation and myth as well as the similarities and differences of signs of racism shown in the film Hidden Figures and the film Just Mercy. This study uses a qualitative research method with semiotic analysis of Roland Barthes. The data obtained by the method of observation, documentation and literature study. The data analysis unit was selected based on the scenes depicting signs of racism as many as 14 scenes, 7 out of 104 scenes from the movie Hidden Figures and 7 out of 119 scenes from the movie Just Mercy. Technique Checking the validity of the data using triangulation. The results of this study indicate that (1) the meaning of denotation, real examples of attitudes, behaviors and words or acts of racism that black people get from white people. (2) The meaning of connotation, it is seen that white people still look down on black people. (3) The meaning of myths, how ideologies and stereotypes are passed down from generation to generation. Comparative analysis, which is to see the similarities and differences in the signs of the two films, lies in the issues raised. The difference is, if Hidden Figures tells of discrimination in employment, Just Mercy tells of discrimination in the legal justice system for black citizens. Both films demonstrate the behavior that is displayed to explain the current type of racism generated by history and global society. Keywords: Comparative Analysis, Meaning, Racism, Film